2012
DOI: 10.5755/j01.ee.23.2.1548
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitude of Risk and Benefits toward Genetically Modified (GM) Foods in South Korea: Implications for Food Policy

Abstract: With highly negative publicity, GM food marketing in South Korea has become a major challenge for potential marketers who are interested in entering the South Korean market. Several consumer groups and non-government organizations (NGOs) in South Korea initiated anti-GM food campaigns. South Korean consumers are reported to be more concerned about potential risk associated with GM food compared to counterpart consumers in the U.S and Europe (KFDA, 2009). Many South Korean food processors and marketers are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…The demographic profile of the respondents was analyzed and the results presented as means, maximum, minimum and their standard deviations. This approach was also used in studies of consumer perception of GM foods (Oladele and Akinsorotan, 2007;Kim, 2012). Furthermore inferential statistics like Chi-square test of independence was used to test the relationship between the categorical responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic profile of the respondents was analyzed and the results presented as means, maximum, minimum and their standard deviations. This approach was also used in studies of consumer perception of GM foods (Oladele and Akinsorotan, 2007;Kim, 2012). Furthermore inferential statistics like Chi-square test of independence was used to test the relationship between the categorical responses.…”
Section: Discussionmentioning
confidence: 99%
“…The debate is largely driven by negative perceptions from consumers about the uncertain effects of GM foods on human health, religious and ethical concerns about taking in foreign gene (Chen and Chen, 2002), concerns on wildlife and environment (Deffor, 2014), and issues on the measures for identification which widely prompted demand for labelling of GM food in many countries in the world (Chen and Chen, 2002). Some debatable issue in many countries are on low awareness and lack of information (Han 1995) while others are cautious of the experts and regulatory bodies of GM foods (Kim, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…dioxin), and unconventional agents such as prions associated with bovine spongiform encephalopathy in cattle." With increasing incidents of outbreaks of food-borne illnesses in market-chains, consumers in developed markets with high levels of imports tend to consider the immediate and future health effects of consumption (Kim, 2012).…”
Section: Health Benefitsmentioning
confidence: 99%
“…However, other research suggests that there is a direct positive association between knowledge about GM food and consumer attitudes: Moerbeek and Casimir () are reluctant to claim a clear positive relationship between consumers’ acceptance of GM food and their understanding of the topic but reported that knowledge does lead to a higher acceptance of GM food, particularly among men. A more recent study suggests that ‘educating’ consumers about GM food would address their concerns and therefore ‘improve’ their negative attitudes towards GM food (Kim, ).…”
Section: Gm Food Controversy: a Post‐normal Science Case Studymentioning
confidence: 99%